2008
DOI: 10.1016/j.ceca.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

GABA release by basket cells onto Purkinje cells, in rat cerebellar slices, is directly controlled by presynaptic purinergic receptors, modulating Ca2+ influx

Abstract: In many brain regions, Ca(2+) influx through presynaptic P2X receptors influences GABA release from interneurones. In patch-clamp recordings of Purkinje cells (PCs) in rat cerebellar slices, broad spectrum P2 receptor antagonists, PPADS (30microM) or suramin (12microM), result in a decreased amplitude and increased failure rate of minimal evoked GABAergic synaptic currents from basket cells. The effect is mimicked by desensitizing P2X1/3-containing receptors with alpha,beta-methylene ATP. This suggests presyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
1
29
3
1
Order By: Relevance
“…The reason for this discrepancy between our results and the results of Donato et al (2008) is not known. It is notable, however, that we directly studied the effect of ATP, whereas Donato et al (2008) We have shown that activation of P2X transmitter-gated ion channels leads to calcium-dependent and CB1 receptordependent retrograde signalling. Although endocannabinoids were not chemically detected in the present study, it is very likely that the retrograde signalling was mediated by endocannabinoids produced by postsynaptic Purkinje cells.…”
Section: Figurecontrasting
confidence: 53%
See 1 more Smart Citation
“…The reason for this discrepancy between our results and the results of Donato et al (2008) is not known. It is notable, however, that we directly studied the effect of ATP, whereas Donato et al (2008) We have shown that activation of P2X transmitter-gated ion channels leads to calcium-dependent and CB1 receptordependent retrograde signalling. Although endocannabinoids were not chemically detected in the present study, it is very likely that the retrograde signalling was mediated by endocannabinoids produced by postsynaptic Purkinje cells.…”
Section: Figurecontrasting
confidence: 53%
“…Thus, it is unlikely that the somatodendritic stimulant ATP effects confounded the inhibitory ATP effects on the axon terminals of interneurones. Donato et al (2008) observed a presynaptic inhibition of interneurone -Purkinje cell transmission by the antagonist PPADS and after desensitization of P2X receptors. It was assumed that endogenous ATP tonically activates P2X receptors on axon terminals of GABAergic interneurones.…”
Section: Figurementioning
confidence: 99%
“…It has been suggested that endogenously released ATP acts at postsynaptic P2XRs to mediate synaptic currents in the hippocampus (Edwards et al, 1992). This classical view, however, is challenged by a series of recent studies that showed that ATP acts rather as a modulator that stimulates the release of other neurotransmitters (Li et al, 1998;Sperlagh et al, 2002;Watano et al, 2004;Rodrigues et al, 2005;Kodama et al, 2007;Sperlagh et al, 2007;Donato et al, 2008). In the SON neurons, for instance, all spontaneous synaptic currents were inhibited by blockers of glutamate and GABAA receptors and application of ATP stimulated about 2300 % increase in frequency of both spontaneous inhibitory and excitatory postsynaptic currents without changes in their amplitude (Fig.3) (Vavra et al, 2011).…”
Section: Modulation Of Glutamate and Gaba Release By Presynaptic P2xrsmentioning
confidence: 86%
“…PPADS-sensitive P2X2Rs have been shown in glutamatergic terminals of neurons in trigeminal mesencephalic motor nucleus (Khakh and Henderson, 1998), the nucleus tractus solitari (Shigetomi and Kato, 2004) and the area postrema (Kodama et al, 2007). The presynaptic P2X2Rs have been shown to underlie increase in GABA release in a subset of GABAergic interneurons in the spinal cord (Hugel and Schlichter, 2000) and in Purkinje cells in rat cerebellar slices (Donato et al, 2008). In SON neurons, the ATP-induced increases in the frequency of spontaneous excitatory and inhibitory postsynaptic currents were also inhibited by PPADS and potentiated by pH 6.5, indicating the involvement of presynaptic P2X2Rs in the release of both neurotransmitters (Vavra et al, 2011).…”
Section: Modulation Of Glutamate and Gaba Release By Presynaptic P2xrsmentioning
confidence: 99%
“…Even in the cases where such transmission occurs, the resulting postsynaptic responses are so small that complete blockade of principal glutamatergic transmission and extremely strong presynaptic stimulation are required to detect them [80,81]. Rather, in a large variety of central structures, degradation-resistant P2X receptor agonists such as , -methylene ATP robustly facilitate release of transmitters such as glutamate and GABA, mostly through direct Ca 2+ entry through presynaptic P2X receptors [82][83][84][85][86][87][88], suggesting that the major site of action for the extracellular ATP in CNS neurons in situ is in presynaptic structures.…”
Section: Diverse Effects Of Exogenous Purines In Brain Slicesmentioning
confidence: 99%